2007
DOI: 10.1042/cs20060260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic CB1 cannabinoid receptor antagonism on livers of rats with biliary cirrhosis

Abstract: Recent studies have shown that the activated endocannabinoid system participates in the increase in IHR (intrahepatic resistance) in cirrhosis. The increased hepatic production of vasoconstrictive eicosanoids is involved in the effect of endocannabinoids on the hepatic microcirculation in cirrhosis; however, the mechanisms of these effects are still unknown. The aim of the present study was to investigate the effects of chronic CB(1) (cannabinoid 1) receptor blockade in the hepatic microcirculation of CBL (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 50 publications
(70 reference statements)
2
40
0
Order By: Relevance
“…Chronic treatment with AM251 produced the same vascular effects in conjunction with decreases in hepatic collagen production, transforming growth factor-␤, and several markers of the phospholipase A 2 eicosanoid system (22). The portal hypotensive effect in that study may therefore have been partly mediated by the decreased liver fibrosis in addition to reduced portal venous inflow.…”
Section: Splanchnic Hemodynamicsmentioning
confidence: 64%
See 2 more Smart Citations
“…Chronic treatment with AM251 produced the same vascular effects in conjunction with decreases in hepatic collagen production, transforming growth factor-␤, and several markers of the phospholipase A 2 eicosanoid system (22). The portal hypotensive effect in that study may therefore have been partly mediated by the decreased liver fibrosis in addition to reduced portal venous inflow.…”
Section: Splanchnic Hemodynamicsmentioning
confidence: 64%
“…Anandamide effects in the mesenteric circulation are also very concordant in all studies to date. In supraphysiological doses, it increases superior mesenteric arterial flow in cirrhotic rats without any significant effect in controls, an effect blocked by AM251 or SR141716 preadministration (16,22). During anandamide infusion, BDL mesenteric venules also significantly dilate but less prominently than the arterioles.…”
Section: Splanchnic Hemodynamicsmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies have shown significant antifibrogenic effects of CBR ligands in liver [22,23,24,26,27,30]. However, the effects of CBR ligands on peritoneal tissue have not been examined in the past until a recent study reported that the CB 2 R agonist was able to reduce the peritoneal macrophage number in a murine peritonitis model induced by thioglycollate, an AGE derivative [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also showed that the CBR plays an important role in liver fibrogenesis [21,22,23,24,25]. Moreover, hepatic fibrosis may be rescued by the knockout of the CB 1 R gene or by administration of the CB 1 R antagonist [24,26,27]. CB 2 R, on the other hand, are located on immune cells and modulate cytokine release [28,29].…”
Section: Introductionmentioning
confidence: 99%